A new species of Oviparosiphidae (Hemiptera: Aphidomorpha) from the Lower Cretaceous of China. (July 2017) - Fu, Ying; Yao, Yunzhi; Qiao, Gexia; Zhao, Yunyun; Ren, Dong
Abstract: A new species Oviparosiphum stictum sp. nov. is described and assigned to the extinct family Oviparosiphidae from the Lower Cretaceous of Yixian Formation at the Huangbanjigou, Beipiao City, Liaoning, China. Well-developed ovipositors in several extinct families of Mesozoic aphids further demonstrates that oviparity is a plesiomorphic state.